ANALISIS KELAYAKAN TEKNIS DAN EKONOMIS PADA PENGERINGAN BIJI KENARI (Canarium Indicum L.) DENGAN MENGGUNAKAN ALAT PENGERING TIPE CABINET DRYER - Risnawati, Risnawati; Rais, Muhammad; Lahming, Lahming (Jurnal Pendidikan Teknologi Pertanian, 2017)
The aims of this study is to determine the feasibility technical and economical drying of canarium nut using a cabinet dryer. This experimental design used was Completely Randomized Design factorial consisted of two factors. The first factor was drying temperature that consisted of three levels: 55OC, 60OC and 65OC. The second factor was drying time that consisted of three levels: 6 hours, 8 hours and 10 hours. Results of the study showed that drying of canarium nut using a cabinet dryer was feasible from the technical and economical aspects. The technical analysis that the quality of canarium nut the best treatment was obtained at the drying temperature of 55OC and drying time 6 hours had water content of 6,8648%, fat content of 62,54%, proteins of 14,47% and yield of 84,75%. The economical analysis resulted on B/C ratio of 1,24, NPV of Rp 284.294.897, IRR of 24%, BEP was reached at the level of production of 99,89 kg canarium nut per month and PBP was reached within 22,38 months.